Comparison of the Effectiveness of Neurocognitive Rehabilitation Program and Acceptance and Commitment Therapy on Metacognitive Skills, Executive Functions, and Emotion Regulation in Women with Breast Cancer - Rafiepoor, Amin; Karfeh Raveshi, Fatemeh; Moghimi, Saranaz (Psychology of Woman Journal, 2025)
Objective: This study aimed to compare the effectiveness of Neurocognitive Rehabilitation Program (NRP) and Acceptance and Commitment Therapy (ACT) on metacognitive skills, executive functions, and emotion regulation in women with breast cancer.Methods and Materials: A randomized controlled trial (RCT) design was used, with 45 women with breast cancer from Tehran randomly assigned to three groups: NRP (n = 15), ACT (n = 15), and a control group (n = 15). The interventions lasted for eight to twelve weeks, and assessments were conducted at pre-test, post-test, and five-month follow-up. Standardized measures were used, including the Metacognitive Awareness Inventory (MAI), Behavior Rating Inventory of Executive Function-Adult Version (BRIEF-A), and Difficulties in Emotion Regulation Scale (DERS). Data were analyzed using repeated-measures ANOVA with Bonferroni post-hoc tests in SPSS-27.Findings: Both NRP and ACT significantly improved metacognitive skills, executive functions, and emotion regulation over time (p < 0.05) compared to the control group. The NRP group showed slightly greater improvements in executive functions, whereas the ACT group demonstrated slightly higher effectiveness in emotion regulation, but these differences were not statistically significant (p > 0.05). The control group did not exhibit significant changes in any variable. No significant differences between NRP and ACT were found, suggesting both interventions are equally effective in addressing cognitive and emotional challenges in breast cancer patients.Conclusion: These findings suggest that both interventions can be used as viable psychological treatments for improving cognitive flexibility, self-regulation, and emotional resilience in this population.